The problem of compensation and moral economies of climate change - Rebecca Elliott (economic sociology_the european electronic newsletter, 2021)
The climate crisis is here. Wildfires, running hotter and longer, burn homes to ash. Storms dump more water, faster, onto areas that have been paved over and built up, submerging private property and public infrastructure. Already-observed sea level rise has eaten away at coastal shorelines and generated "sunny-day" flooding from high tides, disrupting normal routines. So who pays for all this loss and damage, and how much?
Keywords: 300